Pengembangan Rumah Kreatif Melalui Pembuatan Miniatur Pikulan Di Desa Tuyuhan Kecamatan Pancur Kabupaten Rembang - Rikah Rikah; Linda Febrianti; Sulasmining Sulasmining; Ari Susanti (Jurnal Pengabdian Masyarakat STIE Surakarta, 2023)
The purpose of this community service is to introduce creative homes through making miniature pegs, namely by providing knowledge about entrepreneurship and making miniature pegs, making stickers, creating business manager Google accounts and Instagram social media accounts, to registering business locations on Google Maps. . The problems faced by partners include a lack of knowledge about entrepreneurship and making miniature poles, no stickers have been made, there is no Google account for business management and social media accounts, and the business location has not been registered. The results of the implementation of this community service program include: entrepreneurship training, making miniature poles, making stickers, creating business manager Google accounts and Instagram social media accounts as marketing media, and registering business locations on Google maps to make it easier to find addresses.